The Influence of Company Size, Public Accounting Firm Reputation, and Audit Opinion on Audit Delay - I Gusti Ayu Sintya Dewi; I Made Pande Dwiana Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Timeliness in financial reporting is a critical aspect for companies as it influences stakeholders’ decision-making. However, in practice, there is often a time gap between the end of the fiscal year and the date the audit report is issued, commonly referred to as audit delay. This study aims to analyze the effect of company size, public accounting firm (PAF) reputation, and audit opinion on audit delay. The research method employed is quantitative with secondary data sources. The sample consists of 89 observations from 16 healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The analytical technique used in this study is multiple linear regression analysis. The findings show that company size and audit opinion have a negative and significant effect on audit delay, supporting the agency theory applied in this study. Meanwhile, the reputation of the public accounting firm has no significant effect on audit delay, which is not in line with the agency theory.